Ubiquitous atmospheric contamination by tobacco smoke: Nicotine and a new marker for tobacco smoke-derived particulate matter, nicotelline. (May 2021) - Aquilina, Noel J.; Havel, Christopher M.; Cheung, Polly; Harrison, Roy M.; Ho, Kin-Fai; Benowitz, Neal L.; Jacob III, Peyton
Graphical abstract: Highlights: Nicotelline is ubiquitous and easily detected in airborne PM. Particulate nicotelline is directly proportional to total (particle+gas phase) nicotine. Nicotelline exhibits geographical variability linked to population density and population prevalence of tobacco use. The percentage of tobacco smoke particulate in airborne PM varies from 0.03% to 0.08% Nicotelline can be used as a marker of tobacco smoke particulate in airborne PM. Abstract: Second Hand Smoke (SHS) has always been primarily linked with indoor pollution. To date nicotine was the favoured marker for SHS alongside measurements of particulate matter (PM) levels. As nicotine is mainly found in the gas-phase and reactive in the outdoor environment it is not ideal as a marker for the SHS-driven particulate component in PM. Nicotelline, a minor tobacco alkaloid that is stable, found almost exclusively in the particle phase and easy to quantify even at low concentrations, is being proposed as a better marker. It is the first study using bisulfate-treated quartz fiber filters to show that airborne nicotine (gas+particle phase) is directly proportional to airborne nicotelline in countries that have different climates. The analytical method developed has been validated to show that the use of untreated filters is suitable for the quantification of nicotelline even at low concentrations. Although nicotelline exhibits a seasonal and geographical variation, this is the first comprehensive study which demonstrates the ubiquitous presence of nicotelline in PM from outdoor air samples collected in the USA (0.1–285.6 pgm −3 ), UK (2.3–9.1 pgm −3 ), Hong Kong (3.8–109.3 pgm −3 ) and Malta (4.2–280.8 pgm −3 ). From the nicotelline apportionment factor of 1589 ng/mg of tobacco smoke PM we estimate the fraction of outdoor airborne PM derived from SHS to be in the range of 0.03–0.08%. While it is unlikely for tobacco smoke-related toxics in outdoor PM to be considered a major health hazard, in heavily polluted microenvironments this marker would be useful in tracing the presence of SHS and emerging Third Hand Smoke components that form or are found in airborne and settled PM that could induce serious health effects.